SMART TECHNOLOGIES FOR RURAL TRANSFORMATION: A MULTISECTORAL STUDY OF AI, IOT, BLOCKCHAIN, AND AR/VR ADOPTION IN HEALTHCARE, FOOD SYSTEMS, AND ECO-TOURISM - Khanna, Kanika (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Research evaluates the implementation and consequences of contemporary technologies in combination with telemedicine and wearable devices along with blockchain and IoT sensors and GIS and AR/VR while considering stakeholder needs centered on accessibility and scalability and sustainability. A survey of 240 rural stakeholders from Jharkhand, Rajasthan and Himachal Pradesh demonstrates the fundamental conclusions. The findings show that internet infrastructure directly influences telemedicine adoption since 82% of healthcare providers enabled telemedicine in areas with connected infrastructure but this rate reduced to 45% in regions with limited internet access. The high cost of wearable devices combined with their limited ability to integrate into existing healthcare systems (55% and 45% of respondents respectively) prevent wider adoption in chronic disease management. Due to data privacy concerns and a lack of specialized expertise AI-driven diagnostics achieved a 75–80% increase in diagnostic accuracy yet remained slow to gain wide acceptance. Blockchain technology adoption reached 20% in rural food systems which resulted in a 40% increase of item traceability along with a 30% decrease in food-related fraud. IoT sensors became popular with 50% of suppliers yet their adoption remained limited by both high costs which affected 70% of suppliers and insufficient technical knowledge which prevented 50% of suppliers from implementing them. Our analysis demonstrates GIS-based approaches provided :78% biodiversity benefits in Manali during this research period while areas without GIS technology achieved :48% biodiversity benefits. Sixty percent of operators reported that AR/VR adoption improved tourist engagement yet faced issues regarding expensive energy use (70%) and limited affordability (60%). Data reveals critical systemic issues which combine insufficient infrastructure with affordability problems and policy weaknesses and that require strategic financial support and capability development projects to address. This study demonstrates actionable strategies for rural technology adoption using stakeholder-relevant values of inclusivity and sustainability which supports development across health, food systems and eco-tourism through strategic gap bridging endeavors.